Comment: Decision-Making in Latin American Business - Prasad, Shailendra (Academy of Management Journal, 1965)
In response to an earlier article in this journal by Eugene Mccann titled “An Aspect of Management Philosophy in the United States and Latin America,” the article discusses management in Latin Amer...